Analisis Hambatan dan Bentuk Tanggung Jawab Dalam Proses Pengiriman Shopee Express - Meza Putri Alfiana; Syuryatman Desri; Venia Dwi Ayu Sarahita; Cindy Putri Sabrina; Reza Mahera Chaniago (Fakultas Ekonomi Universitas 45 Surabaya, 2024)
Indonesia has experienced tremendous growth in terms of technological advancement, especially e-commerce. People now have more options to use expedition services thanks to the growth of e-commerce. One of the expedition services that is directly connected to Shopee is Shopee Express. However, Shopee Express is still widely complained about by customers regarding the obstacles to shipping goods. Therefore, Shopee Express needs to pay attention to the quality of services and responsibilities provided so as not to harm consumers. The purpose of this study is to analyze the obstacles and forms of responsibility in the Shopee Express delivery process. The research method used is the type of Empirical Legal research with a qualitative approach, with the hope of analyzing regulations, identifying, and adjusting them to conditions in the field. The results of this study indicate that the Shopee Express delivery procedure starts from inputting when the buyer checks out, the input step in sending the package by collecting complete data about the package from the buyer, such as the delivery address, package observation, until the package delivery process by the Shopee Express operational team to the buyer. Some of the obstacles faced by Shopee Express are delays in shipping goods, accumulation of consumer goods in the expedition warehouse, damage to goods referring to physical damage, loss of package contents. In order to overcome the obstacles in shipping goods/packages through Shopee Express, some solutions that can be implemented include providing regular rewards or cashback as incentives.